Improved sexual history taking in the 2012 BASHH asymptomatic screening re-audit. (April 2014) - Menon-Johansson, AS; McClean, H; Carne, CA; Estreich, S; Knapper, C; Sethi, G; Smith, A; Sullivan, AK
Effective asymptomatic screening for sexually transmitted infections is an important public health service because a significant proportion of sexually transmitted infections do not present with symptoms. In 2009, the National Audit Group of the British Association of Sexual Health and HIV (BASHH) audited the management of asymptomatic patients and recommended increased documentation about oral and anal sex, regional strategies for nucleic acid amplification test (NAAT) use for gonorrhoea, improved screening for hepatitis B in men who have sex with men and an increase in screening for HIV. The 2012 audit used web-based forms to collect submissions from 180 consultant-led centres (65% response rate) that included episodes of care from 6669 asymptomatic patients. An improvement was demonstrated for all the areas measured during the 2009 audit. A doubling of gonorrhoea testing using NAATs was seen and yet 10% of asymptomatic patients continued to have microscopy despite these tests not being recommended by BASHH guidelines. This audit recommends universal adoption of gonorrhoea NAATs across the United Kingdom.